PERSPECTIVES OF UNDERSTANDING AND IMPLEMENTATION OF INFORMATION MODELLING TECHNOLOGIES IN THE CONTEXT OF RESTORATION OF ARCHITECTURAL MONUMENTS - D. Kamalova (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2024)
The article is devoted to the analysis of the purpose and peculiarities of application of the latest technology of building information modelling (BIM) when working with architectural monuments. BIM technology at its creation was aimed primarily at the design and construction industry, but its application in historical and architectural work can fundamentally change in the direction of better storage and processing of huge amounts of information, and this type of activity. By means of comparative analysis, the following are considered: the relationship between the components of the information model of an architectural monument, the peculiarities of creating such a model, the necessity and importance of developing libraries of elements for historical buildings. Special attention is paid to the cultural connection through BIM of past epochs and modern architecture. It also considers the prospects for the application of BIM-technologies in the context of reconstruction and restoration of buildings and monuments of architecture.